Ultrathin, flexible and multimodal tactile sensors based on organic field-effect transistors - Fabrizio Antonio Viola (Nature Portfolio, 2018)
Abstract In this study, a novel approach to the fabrication of a multimodal temperature and force sensor on ultrathin, conformable and flexible substrates is presented. This process involves coupling a charge-modulated organic field-effect transistor (OCMFET) with a pyro/piezoelectric element, namely a commercial film of poly-vinylene difluoride (PVDF). The proposed device is able to respond to both pressure stimuli and temperature variations, demonstrating the feasibility of the approach for the development of low-cost, highly sensitive and conformable multimodal sensors. The overall thickness of the device is 1.2 μm, being thus able to conform to any surface (including the human body), while keeping its electrical performance. Furthermore, it is possible to discriminate between simultaneously applied temperature and pressure stimuli by coupling sensing surfaces made of poled and unpoled spin-coated PVDF-trifluoroethylene (PVDF-TrFE, a PVDF copolymer) with OCMFETs. This demonstrates the possibility of creating multimodal sensors that can be employed for applications in several fields, ranging from robotics to wearable electronics.